Perancangan Pengendalian Bahaya Pada PT. Alpha Graha Industri - Vincent Khosasi; Togar Wiliater Soaloon Panjaitan (Jurnal Titra, 2023)
PT. Alpha Graha Industri is a company that produces alpha carts. There havebeen several work accidents at the production site of PT. Alpha Graha Industries. This final assignment was carried out using direct observation methods and interviews with company owners and local workers. The purpose of this final project is to reduce the number of work accidents at PT. Alpha Graha Industries. From the results of the analysis that occurred, it was found that 22 activities in the production process had risk analysis values of 59% high, 13.7% moderate and 27.3% low which could cause work accidents. 32 risk control proposals have been proposed which are dominated by 50% technical engineering, 34.4% Personal Protective Equipment and 15.6% administration.The proposal given by the author has been approved by the company. It is predicted that the risk rating of the activities will be 100% low.